2023
DOI: 10.1111/ijfs.16276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two kinds of Bacillus on flavour formation of Baijiu solid‐state fermentation with pure mixed bacteria

Abstract: Bacillus plays a unique role in Baijiu brewing, but its functions have not been fully explored. In this study, Aspergillus niger, Saccharomyces cerevisiae and Thermoactinospora rubra were used as chassis microorganisms in a fermentation system. Bacillus subtilis and Bacillus licheniformis, which are common in Maotai-flavoured Baijiu, were studied in the fermentation. Their metabolic differences and effects on the formation of Baijiu flavour in the process of stacking fermentation were analysed. The combined fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Also, there are a wide range of aromas, mostly recognized by their similarity to quite defined chemical compounds, such as various alcohols, a multiplicity of terpenes, esters, aldehydes, and ketones (Supplementary Table S1). All of them leave a unique chemical imprint on traditional distillates; in contrast, most commercial distillers, since they control the fermentation and therefore the microorganisms that carry it out, are more committed to producing distillates with higher alcohol contents with very few flavors and aromas [29]. That is why these organoleptic characteristics place distillates in three different categories according to their chemical contents.…”
Section: Discussionmentioning
confidence: 99%
“…Also, there are a wide range of aromas, mostly recognized by their similarity to quite defined chemical compounds, such as various alcohols, a multiplicity of terpenes, esters, aldehydes, and ketones (Supplementary Table S1). All of them leave a unique chemical imprint on traditional distillates; in contrast, most commercial distillers, since they control the fermentation and therefore the microorganisms that carry it out, are more committed to producing distillates with higher alcohol contents with very few flavors and aromas [29]. That is why these organoleptic characteristics place distillates in three different categories according to their chemical contents.…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus had strong saccharification ability as well as generating a variety of enzymes, with a great catalytic ability for macromolecule degradation such as starch and proteins, which has positively contributed to Baijiu quality. Studies have also shown that Aspergillus can also inhibit the growth of harmful microorganisms by producing acidic proteases to lower pH, which also ensures the relative safety of Baijiu [23]. Interestingly, the relative abundance of the Trametes genus remained zero in stages D-1 and D-2; the highest value appeared in stage D-3 (less than 1%).…”
Section: Relative Abundance Of Fungal Communitiesmentioning
confidence: 99%
“…Bacillus subtilis and Bacillus licheniformis cooperate with Aspergillus Niger and Saccharomyces Cerevisiae to enrich flavor system of white wine. Tetramethylpyrazine produced by Bacillus gives the white wine a nutty flavor ( Wang et al, 2023 ).…”
Section: Types and Characteristics Of Microorganism Producing Flavor ...mentioning
confidence: 99%